Legal Change and Sentencing Norms in the Wake of Booker: The Impact of Time and Place on Drug Trafficking Cases in Federal Court. Issue 2 (June 2014) - Lynch, Mona; Omori, Marisa
<x xml:space="preserve">Abstract</x> The federal sentencing guidelines have lost some authoritative force since the U.S. Supreme Court ruled in a series of recent cases that the guidelines are advisory, rather than presumptive, in determining criminal sentences. While these court decisions represent a dramatic legal intervention, sociolegal scholarship suggests that organizational norms are likely to change slowly and less dramatically than the formal law itself. The research reported here looks specifically at the consequences of such legal transformations over time and across locale, using multilevel analysis of U.S. Sentencing Commission sentence outcome data from 1993 to 2009. Our findings suggest that districts vary considerably from each other in sentencing practices over the time period studied, and that there is relative within‐district stability of outcomes within districts over time, including in response to the Supreme Court's mandates. We also find that policy change appears to influence the mechanisms by which cases are adjudicated in order to reach normative outcomes. Finally, we find that the relative district‐level reliance upon mandatory minimums, which were not directly impacted by the guidelines changes, is an important factor in how drug trafficking cases are adjudicated. We conclude that local legal practices not only diverge in important ways across place, but also become entrenched over time such that top‐down legal reform is largely reappropriated and absorbed into locally established practices.